Revisit to carbon monoxide oxidation on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
Carbon monoxide (CO) oxidation on Pd(111) surfaces has been studied by molecular beam methods with mixed molecular beams (CO + O(2)) between 400 and 900 K and a CO:O(2) ratio of 7:1 to 1:10. A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd(111) subsurface layers and its significant influence toward CO oxidation at high temperatures (>= 600 K). An overall influence of subsurface oxygen on the kinetics of the CO oxidation reaction is addressed. Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(Osub)), above which the reactive CO adsorption occurs on the surface with subsequent CO(2) production. The above observation Was demonstrated with CO-rich reactant compositions (CO + O(2)) above 600 K via instant oxygen adsorption on Pd surfaces; however, onset of CO adsorption as well as CO(2) production occurs after a time delay. theta(Osub) and the time delay in CO adsorption (and CO(2) production) increase with increasing temperature and with CO-rich compositions. theta(Osub) was measured up to 0.3 monlayer (ML) between 500 and 850 K before the onset of CO adsorption; however, theta(Osub) increases from an insignificant value at <500 K to 0.4 ML at 900 K with a pure O(2) beam. Onset of CO adsorption with a significant sticking coefficient on the Pd surfaces, that is, covered with significant subsurface oxygen, underscores a change in the electronic state of Pd surfaces toward mildly oxidized (or Pd(delta+)), and an electronic decoupling occurs between the bulk and the surface. The jellium model is invoked to demonstrate the changes observed. A similar observation with polycrystalline Pd surfaces suggests the defect sites is one of the channels for oxygen diffusion into subsurfaces. Initial sticking coefficient (s(0)) measurements demonstrate that there is no significant competition between CO and O(2) adsorption from the CO + O(2) mixture between 400 and 600 K, and indeed they are largely independent of each other. The maximum steady-state CO(2) formation rate was observed for a 1:1 CO/O(2) beam composition between 500 and 550 K. However, with a significant theta(Osub) the rate of CO(2) Production in the steady state is considerable even at high temperatures (700-850 K), and a broadening of the active CO oxidation regime to high temperature is observed with O(2)-rich compositions.

Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.

Role of nanointerfaces in Cu- and Cu plus Au-based near-ambient-temperature CO oxidation catalysts - Gnanakumar, Edwin S.; Naik, Jarpla Madhusudhan; Manikandan, Marimuthu; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Disordered mesoporous Cu-doped ceria-zirconia (Cu0.1Ce0.85Zr0.05O2), and gold deposited (Au/Cu0.1Ce0.85Zr0.05O2) catalysts were synthesized and evaluated for CO oxidation. Onset of CO oxidation activity, and 50% (100%) CO2 formation occurs at room temperature (RT), and 77 (120)degrees C, respectively, with Cu0.1Ce0.85Zr0.05O2. A small amount of gold on Cu0.1Ce0.85Zr0.05O2 induces the sustainable oxidation catalysis around RT. Onset of copper reduction temperature decreases from 110 degrees C on Cu0.1Ce0.85Zr0.05O2 to 48 degrees C with Au/Cu0.1Ce0.85Zr0.05O2, highlighting the direct interaction between Cu and Au through a Cu-Au interface. Au particles with a (00 1) facet deposit on an oxygen-deficient site of (111) facet of CeO2-ZrO2. Any decrease in surface Cu-content with increasing Au-content further supports the Au-Cu-Ce/Zr interface interactions. Nanointerfaces of Au clusters on Cu next to oxygen-deficient sites of CeO2-ZrO2 facilitate all the elementary steps of the CO + O-2 reaction to occur in close proximity at ambient conditions.
Keywords: carbon monoxide; Gold; heterogeneous catalysis; Oxidation; redox

Rational approach towards enhancing solar water splitting: a case study of Au-RGO/N-RGO-TiO2 - Bharad, Pradnya A.; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Nanoscale, 2015)
A rational approach was employed to enhance the solar water splitting (SWS) efficiency by systematically combining various important factors that helps to increase the photocatalytic activity. The rational approach includes four important parameters, namely, charge generation through simulated sunlight absorption, charge separation and diffusion, charge utilization through redox reaction, and the electronic integration of all of the above three factors. The complexity of the TiO2 based catalyst and its SWS activity was increased systematically by adding reduced graphene oxide (RGO) or N-doped RGO and/or nanogold. Au-N-RGO-TiO2 shows the maximum apparent quantum yield (AQY) of 2.46% with a H-2 yield (525 mu mol g(-1) h(-1)) from aqueous methanol, and overall water splitting activity (22 mu mol g(-1) h(-1); AQY = 0.1%) without any sacrificial agent under one sun conditions. This exercise helps to understand the factors which help to enhance the SWS activity. Activity enhancement was observed when there is synergy among the components, especially the simulated sunlight absorption (or one sun conditions), charge separation/conduction and charge utilization. Electronic integration among the components provides the synergy for efficient solar light harvesting. In our opinion, the above synergy helps to increase the overall utilization of charge carriers towards the higher activity.

Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting